Influence of alternative husbandry systems on postmortem findings and prevalence of important bacteria and parasites in layers monitored from end of rearing until slaughter. (24th March 2018) - Zloch, Angelika; Kuchling, Sabrina; Hess, Michael; Hess, Claudia
Abstract : In the present study 66 layer flocks housed in different alternative husbandry systems were monitored from placement of birds on the farm until slaughter to evaluate a possible influence on the occurrence of selected non‐infectious as well as infectious diseases. Postmortems were performed and the occurrence of extraintestinal Escherichia coli and Gallibacterium anatis was investigated. No specific postmortem findings were seen in pullets. Non‐infectious diseases were mainly found in layers. Most prominent postmortem findings in layers were reproductive tract lesions and the presence of intestinal helminths. From each flock E coli and from approximately 65 per centof the flocks G anatis were isolated. No significant differences were seen in regard to the housing system, but the prevalence of G anatis increased with the age of birds. The majority of reproductive tract lesions could be associated with E coli alone or G anatis co‐infections. The prevalence of Ascaridia galli and Heterakis gallinarum was not influenced by the housing system, but significantly increased with age. Cestodes were present in six flocks. Histomonosis was detected twice. Dermanyssus gallinae was found in 5 pullet and 20 layer flocks. Additional investigations were performed on demand. Again, reproductive tract lesions were the most prominent postmortem findings. In one flock each histomonosis or erysipelas was diagnosed, respectively. Severe affection by D gallinae was found once. Necrotic enteritis was seen in two layer flocks.